Kinetics of the gas phase reaction of the Criegee intermediate CH2OO with SO2 as a function of temperature. Issue 35 (8th September 2021) - Onel, Lavinia; Lade, Rachel; Mortiboy, Jennifer; Blitz, Mark A.; Seakins, Paul W.; Heard, Dwayne E.; Stone, Daniel
Abstract : The kinetics of the gas phase reaction of the Criegee intermediate CH2 OO with SO2 have been studied as a function of temperature in the range 223–344 K at 85 Torr using flash photolysis of CH2 I2 /O2 /SO2 /N2 mixtures at 248 nm coupled to time-resolved broadband UV absorption spectroscopy. Abstract : The kinetics of the gas phase reaction of the Criegee intermediate CH2 OO with SO2 have been studied as a function of temperature in the range 223–344 K at 85 Torr using flash photolysis of CH2 I2 /O2 /SO2 /N2 mixtures at 248 nm coupled to time-resolved broadband UV absorption spectroscopy. Measurements were performed under pseudo-first-order conditions with respect to SO2, revealing a negative temperature dependence. Analysis of experimental results using the Master Equation Solver for Multi-Energy well Reactions (MESMER) indicates that the observed temperature dependence, combined with the reported lack of a pressure dependence in the range 1.5–760 Torr, can be described by a reaction mechanism consisting of the formation of a pre-reaction complex leading to a cyclic secondary ozonide which subsequently decomposes to produce HCHO + SO3 . The temperature dependence can be characterised by k CH2OO+SO2 = (3.72 ± 0.13) × 10 −11 ( T /298) (−2.05±0.38) cm 3 molecule −1 s −1 . The observed negative temperature dependence for the title reaction in conjunction with the decrease in water dimer (the main competitor for the Criegee intermediate) concentration at lower temperatures means that Criegee intermediate chemistry can play an enhanced role in SO2 oxidation in the atmosphere at lower temperatures.